Antimicrobial Activity of Chitosan Oligosaccharides with Special Attention to Antiparasitic Potential - da Silva, Nayara Sousa (Mar Drugs, 2021)
The global rise of infectious disease outbreaks and the progression of microbial resistance reinforce the importance of researching new biomolecules. Obtained from the hydrolysis of chitosan, chitooligosaccharides (COSs) have demonstrated several biological properties, including antimicrobial, and greater advantage over chitosan due to their higher solubility and lower viscosity. Despite the evidence of the biotechnological potential of COSs, their effects on trypanosomatids are still scarce. The objectives of this study were the enzymatic production, characterization, and in vitro evaluation of the cytotoxic, antibacterial, antifungal, and antiparasitic effects of COSs. NMR and mass spectrometry analyses indicated the presence of a mixture with 81% deacetylated COS and acetylated hexamers. COSs demonstrated no evidence of cytotoxicity upon 2 mg/mL. In addition, COSs showed interesting activity against bacteria and yeasts and a time-dependent parasitic inhibition. Scanning electron microscopy images indicated a parasite aggregation ability of COSs. Thus, the broad biological effect of COSs makes them a promising molecule for the biomedical industry.